Silencing a Multifunctional microRNA Is Beneficial for Stroke Recovery - Roitbak, Tamara (Frontiers in Molecular Neuroscience, 2018)
Stroke-induced endothelial cell injury leads to destruction of cerebral microvasculature and significant damage to the brain tissue. A subacute phase of cerebral ischemia is associated with regeneration involving the activation of vascular remodeling, neuroplasticity, neurogenesis, and neuroinflammation processes. Effective restoration and improvement of blood supply to the damaged brain tissue offers a potential therapy for stroke. microRNAs (miRNAs) are recently identified small RNA molecules that regulate gene expression and significantly influence the essential cellular processes associated with brain repair following stroke. A number of specific miRNAs are implicated in regulating the development and propagation of the ischemic tissue damage as well as in mediating post-stroke regeneration. In this review, I discuss the functions of the miRNA miR-155 and the effect of its in vivo inhibition on brain recovery following experimental cerebral ischemia. The article introduces new and unexplored approach to cerebral regeneration: regulation of brain tissue repair through a direct modulation of specific miRNA activity.